2021
DOI: 10.1155/2021/9526701
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine Profiles and Immune Response Are Increased in COVID-19 Patients with Type 2 Diabetes Mellitus

Abstract: The induction of inflammation and cytokine storm was proposed to play a critical role in COVID-19. This study is aimed at investigating the relationship between glucose metabolism and the inflammatory state of inpatients with COVID-19. 71 inpatients with COVID-19 were classified into nondiabetes mellitus (NDM) group, impaired fasting glucose (IFG) group, and diabetes mellitus (DM) group. The average hospitalization days were significantly shorter in DM patients when compared with patients in the IFG group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
(44 reference statements)
1
39
0
2
Order By: Relevance
“…Compared to nondiabetic COVID-19 patients, diabetic COVID-19 patients are characterized by a higher percentage of CD4 + T cell and a lower percentage of CD8 + T cells and higher serum levels of IL-6, IL-2, IL-10, and INFγ. Moreover, serum levels of TNFα, IL-4, IL-2, IL-10, and INFγ were significantly higher in the diabetic group than the impaired fasting glucose group [ 36 ]. Whether the typical “cytokine storm” immune response pattern often indicated in COVID-19 is due to viral destruction of immune cells or is due to preexisting underlying conditions in diabetes needs to be distinguished as this would change the approach to treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to nondiabetic COVID-19 patients, diabetic COVID-19 patients are characterized by a higher percentage of CD4 + T cell and a lower percentage of CD8 + T cells and higher serum levels of IL-6, IL-2, IL-10, and INFγ. Moreover, serum levels of TNFα, IL-4, IL-2, IL-10, and INFγ were significantly higher in the diabetic group than the impaired fasting glucose group [ 36 ]. Whether the typical “cytokine storm” immune response pattern often indicated in COVID-19 is due to viral destruction of immune cells or is due to preexisting underlying conditions in diabetes needs to be distinguished as this would change the approach to treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical risk factors for severe COVID-19 cases are poorly classified due to the ever-evolving pool of patient data obtained during the 2020 pandemic. Regardless, age, end-stage organ failure, viral infections, cardiovascular disease, sepsis, obesity, severe immunosuppression, cancer, and poorly controlled or end-stage respiratory diseases are identified as risk factors increasing the morbidity and mortality from a SARS-CoV-2 infection [ 10 , 11 , 12 , 13 ]. The literature presents mixed findings regarding the mortality risk of COVID-19 patients with prior diagnosis of asthma and upper airway diseases [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a delayed and dysregulated response can evolve in some cases resulting in a cytokine storm which can be catastrophic to the patient [ 9 ]. It was demonstrated that several comorbidities including cancer, diabetes and immunodeficiency, are associated with a higher risk of cytokine storm [ 10 , 11 , 12 , 13 ]. Studies showed that type I IFNs (IFNα, IFNβ) and type II IFNs (IFNγ) induced ACE2 expression in nasal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a French study, these complications were significantly associated with an increased risk of mortality in patients with diabetes and COVID-19 comorbidity [ 17 ]. On the other hand, in a Chinese study, patients with COVID-19 and elevated glucose levels showed promoted cytokine profiles and immune responses [ 18 ]. In that study, patients with coexisting diabetes had shorter hospitalisation times [ 18 ].…”
Section: Potential Pathophysiological Mechanisms Existing In Diabetes and Covid-19mentioning
confidence: 99%
“…On the other hand, in a Chinese study, patients with COVID-19 and elevated glucose levels showed promoted cytokine profiles and immune responses [ 18 ]. In that study, patients with coexisting diabetes had shorter hospitalisation times [ 18 ]. The possible explanation for this phenomenon is that increased blood glucose levels might be beneficial for some anti-inflammatory cytokines and for the process of eliminating the virus [ 18 ].…”
Section: Potential Pathophysiological Mechanisms Existing In Diabetes and Covid-19mentioning
confidence: 99%